A high-precision age estimate of the Holocene Plinian eruption of Mount Mazama, Oregon, USA - Egan, Joanne; Staff, Richard; Blackford, Jeff (The Holocene, 2015)
The climactic eruption of Mount Mazama in Oregon, North America, resulted in the deposition of the most widespread Holocene tephra deposit in the conterminous United States and south-western Canada. The tephra forms an isochronous marker horizon for palaeoenvironmental, sedimentary and archaeological reconstructions, despite the current lack of a precise age estimate for the source eruption. Previous radiocarbon age estimates for the eruption have varied, and Greenland ice-core ages are in disagreement. For the Mazama tephra to be fully utilised in tephrochronology and palaeoenvironmental research, a refined (precise and accurate) age for the eruption is required. Here, we apply a meta-analysis of all previously published radiocarbon age estimations (n = 81), and perform Bayesian statistical modelling to this data set, to provide a refined age of 7682–7584 cal. yr BP (95.4% probability range). Although the depositional histories of the published ages vary, this estimate is consistent with that estimated from the GISP2 ice-core of 7627 ± 150 yr BP (Zdanowicz et al., 1999).